Energy Sustainability Performance Index of Biodigester Using Energy LCA-Based Indicators - Kluczek, Aldona; Gladysz, Bartlomiej (Frontiers in Energy Research, 2022)
Nowadays, it is still difficult to measure organizations’ performances due to the complexity of energy systems, their multiple functions, and the usage of unclear indicators. Organizations need to consider energy issues to contribute to sustainability. This paper aims to develop a methodology for measuring energy sustainability performance for a biogas plant, but the idea of the study is to establish to which degree the methodology may be substituted for the traditional methods based on multicriteria decision-making, which are used for sustainability assessment. Hence, the evaluation performance method combines fuzzy numbers, linguistic scale, and energy life-cycle indicators. The evaluation is carried out for the biodigester, presenting its results in terms of energy sustainability performance index for two scenarios (p and q) considering the three-dimensional sustainability structure. The results pictured that the value of energy sustainability performance index q (0.382) is relatively lower than the index achieved for scenario p (0.815). Biodigester for scenario q does not demonstrate a positive perspective on a transition toward energy sustainability. The presented methodology is a new simple method aimed at replacing the current energy performance assessments into a technology evaluation solution considering uncertainties, which is not supported by the software. The suggested energy life cycle analysis indicators could be used to evaluate similarly sized biogas plants across countries. They might be also used for prioritization of plants modeling various energy parameters or inspirational for energy decision-makers to deliver more flexible and reliable outcomes within an uncertain environment.